The Effect of Minimum Wages and Population Number on Unemployment in Jambi Province 2019-2023 - Nurilmi, Besse; Hardi, Eja Armaz; Rafidah, Rafidah (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the effect of minimum wages and population on the unemployment rate in Jambi Province in the period 2019-2023. The method used is panel data regression with the Fixed Effect Model (FEM) approach. The results of the study indicate that partially, minimum wages and population do not have a significant effect on the unemployment rate in Jambi Province. However, simultaneously, both variables have a significant effect on the unemployment rate. This finding indicates that employment policies must not only consider increasing minimum wages, but also create more productive jobs and adjust labor market needs to population growth. Therefore, the government is expected to implement a more comprehensive policy to reduce the unemployment rate